Evolution of millimeter-wave communications toward next generation in wireless technologies - A. Z. Yonis (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Next generation in wireless communication systems being deployed in the world, 5G/6G mobile and wireless communication technologies has been widely studied. This work clarifies that Millimeter-Wave (mm-Wave) is in its early stages and will be driven by consumers who keep on desire higher information rates for the consumption of media. Millimeter-Wave innovation represents for next generation cellular technology and includes a wide range of advanced features which make next innovation most dominant technology in near future, these abilities incorporate high achievable information rates in addition to lower delays and constant connectivity on wireless devices.